Effect of Titanium Oxide Nanofluid Concentration on Pressure Drop - Khamisah, Abdul Hamid; Azmi, W. H.; R., Mamat; N. A., Usri; G., Najafi (Asian Research Publishing Network (ARPN), 2015)
The new technology of nanoparticle has introduced the advance heat transfer fluid called nanofluid. In an automobile engine cooling system, the pumping power has to be considered in order to optimize the overall system. Reflecting to the statement, this paper concentrate on the study of pressure drop for Ethylene Glycol (EG) based nanofluid. The nanofluid is prepared by dilution technique of Titanium Oxide (TiO2) in based fluid of mixture water and ethylene glycol (EG) in volume ratio of 60:40, at three volume concentrations of 0.5 %, 1.0 % and 1.5 %. The experiment was conducted under a flow loop with a horizontal tube test section at various values of flow rate for the range of Reynolds number less than 30,000. The experimental result of TiO2 nanofluid pressure drop is compared with the Blasius equation for based fluid. It was observed that pressure drop increase with increasing of nanofluid volume concentration and decrease with increasing of nanofluid temperature insignificantly.